Epistemologi Tafsir Aurat Perempuan Menurut Hussein Muhammad - Murtaza MZ, Ahmad; Awaluddin, Raisa Zuhra Salsabila; Hasibuan, Kiki Rumonda Rezaki (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2022)
Background. Discussions about the use of headscarves by women seem to force women to cover their genitals completely without seeing the purpose of their use. Through Husein Muhammad's study that there are things that are far more important, namely security for women or men.Aim. This article aims to reveal Husein Muhammad's view of women's genitalia.Methods. This literature study took various reference about women's genitalia, uses an epistemological interpretation analysis framework to discuss the sources, methods, and validity of interpretations.Results. Husein studied women's genitalia based on the Holy Qur'an, Hadith, and ijma' 'ulama by applying five methods, namely: first, making the goal of sharia (maqashidusy sharia) as the main basis of interpretation; second, analyzing the socio-historical aspects (as-Siyaqut taarikhil ijtima’i) of the cases in the text; third, analyzing the language and its context (as-Siyaqul orali); fourth, identifying the causal aspect in the text as an analogical way of thinking for the needs of a new social context, now and here (qiyasul ghaib 'alasy syahid), and; fifth, conducting a critical analysis of the sources of hadith transmission (takhirjul asanid) and criticism of matan (naqdul matn). The validity of Husein's interpretation was tested through the application of three theories of truth, namely coherence, correspondence, and pragmatism.